A Component Based Heuristic Search Method with AdaptivePerturbations for Hospital Personnel Scheduling - Li, Jingpeng; Aickelin, Uwe; Burke, Edmund (2006)
Nurse rostering is a complex scheduling problem that affects hospital personnel on a daily basis all over the world. This paper presents a new component-based approach with adaptive perturbations, for a nurse scheduling problem arising at a major UK hospital. The main